Penerapan RFID pada Aplikasi Pembayaran Nontunai Kantin Sekolah (Studi Kasus: Kantin SD Negeri Gunungpuyuh Cipta Bina Mandiri) - Dahlia Widhyaestoeti; Ricki Hardiyanto; Safarudin Hidayat Al Ikhsan; Jejen Zaenudin (Teknik Informatika Universitas Pamulang, 2023)
The canteen of SD Negeri Gunungpuyuh Cipta Bina serves students and teachers using a cash payment system. This cash payment creates problems for canteen managers, namely having to be ready with change and payment queues. During the Covid-19 pandemic, canteen managers are required to follow health protocols, one of which is to keep a distance to minimize the spread of the virus. An application is needed by canteen managers to change cash transaction activities into non-cash transactions. The application of RFID (Radio Frequency Identification) technology, as well as Web-based applications, are designed to build a cashless payment system. RFID cards are used for non-cash payment instruments instead of cash. Buyers can use an RFID card as a means of payment for transactions in the canteen and fill in the balance at the canteen manager using a Web-based application. NodeMCU-based RFID ESP 8266 is connected via wifi to the database server. The waterfall method is used to design Web-based applications that function to manage transactions and balances. HTML programming language is used to build applications and MySQL software for databases. The process of making the application starts with assembling the RFID module and testing several RFID cards. Testing the wifi connection and the appearance of the application made shows the test results following the expected results. The process of storing data, managing transactions, and managing buyer balances is well recorded in the created database. This non-cash payment application has been successfully created and is running well, judging by the results of all the tests carried out.